(3GdaQGFV GdSQGLjIs - (3eMeO Hf eMeO Hf YHO GdQTjO GdSLGhfOj GdMfaj, SQGL GdOjf CHh WGgQ,J (B598 (3g` s
(3ChdgG (B:s
(3GdMeO ddg MeO GdTGcQjf , hGdUdGI hGdSdGe Ydi NjQ GdHQjI eMeO hBdg GdWjHjf GdWGgQjf bGd QShd Gddg Udi Gddg Ydjg hSde JYdehG GdaQGFV dCfgG fUa GdYde s
(3BNQgG (B:s
(3hdGjQK HYV GdCehGJ ef HYV , hgPG gh GdeNJGQ hbGd Ydi hGHf eSYhO QVi Gddg YfgeG (B: (3jQK HYVge ef HYV EdG eG hQK cd hGMO efge ef eGd UGMHg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B233 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B6 - (3U (B106s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1247s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs